2021
DOI: 10.3390/ijms22115438
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of COVID-19 Pathogenesis, Conventional and Nanomedicine Therapy

Abstract: In late 2019, a new member of the Coronaviridae family, officially designated as “severe acute respiratory syndrome coronavirus 2” (SARS-CoV-2), emerged and spread rapidly. The Coronavirus Disease-19 (COVID-19) outbreak was accompanied by a high rate of morbidity and mortality worldwide and was declared a pandemic by the World Health Organization in March 2020. Within the Coronaviridae family, SARS-CoV-2 is considered to be the third most highly pathogenic virus that infects humans, following the severe acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 194 publications
(209 reference statements)
0
29
0
Order By: Relevance
“…However, all studies agree that the lack of randomised controlled studies, small cohorts, different dosages and vitamin D formulations, non-standardised study conditions and large heterogeneity between the studies hinders the evaluation and conclusions. Especially since studies in preclinical models showed that vitamin D3 inhibits SARS-CoV-2 virus replication in cells [ 69 , 70 ], but affect also other aspects of COVID-19 disease [ 71 ]. Additionally, the analysis of tINIT models proposed that the metabolism of vitamin D3 molecules is changed in different cell types and this could affect the efficacy and availability of vitamin D3 in the body.…”
Section: Discussionmentioning
confidence: 99%
“…However, all studies agree that the lack of randomised controlled studies, small cohorts, different dosages and vitamin D formulations, non-standardised study conditions and large heterogeneity between the studies hinders the evaluation and conclusions. Especially since studies in preclinical models showed that vitamin D3 inhibits SARS-CoV-2 virus replication in cells [ 69 , 70 ], but affect also other aspects of COVID-19 disease [ 71 ]. Additionally, the analysis of tINIT models proposed that the metabolism of vitamin D3 molecules is changed in different cell types and this could affect the efficacy and availability of vitamin D3 in the body.…”
Section: Discussionmentioning
confidence: 99%
“…In ARDS and COPD associated with COVID-19, the hypoxic conditions result in inflammation that may lead to OS. Increased OS leads, as a consequence, to a decrease in nitric oxide (NO) release mainly because ROS interfere with the activity of the NO synthases and cause an inadequate production of tetrahydrobiopterin [54]. Optimal concentrations of O 2 are required for the synthesis of NO by the nitric oxide synthases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, decreased NO following an oxidative burst can stimulate the production of metalloproteinases-2 and -9 that contribute to pulmonary damage [55]. Hypoxia also increases the presence of protons, in a similar way as in a neutral or acidic pH, compromising the stability of ONOO − and decomposing peroxynitrous acid to form nitrates (NO 3 − ) and NO 2 − [54]. ONOO − causes the irreversible process of nitration of tyrosines in proteins, it oxidizes the thiol groups in them [56] and it also lowers the H 2 S concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Although prevalent for a few decades now, nanotechnology has found new relevance in healthcare in the present scenario when COVID-19 controlling and managing pre/post infection consequences are the main priority of health agencies and experts, as illustrated in Figure 1 B. [ [14] , [15] , [16] ].
Figure 1 A) Prospective of NSs-supported approaches and strategies to mitigate COVID-19 viral infections caused by new SARS-CoV-2 variants of concerns (A), Illustration of state-of-art nanosytem investigated for diagnorics, treatment and vaccine delivery to manage COVID-19 efficient (B, Copyright ACS 2021 ).
…”
Section: Introduction: Emergence To Manage Cov-19 Pandemicmentioning
confidence: 99%